Biodegradation of fluorene by neoteric LDPE immobilized Pseudomonas pseudoalcaligenes NRSS3 in a packed bed bioreactor and analysis of external mass transfer correlation. (February 2019) - Sonwani, R.K.; Giri, B.S.; Das, T.; Singh, R.S.; Rai, B.N.
Graphical abstract: Highlights: Immobilization of Pseudomonas pseudoalcaligenes NRSS3 (MF992192) on LDPE. Biodegradation of fluorene in continuous packed bed bioreactor. Effect of flow rates on external mass transfer. GC–MS analysis confirmed the biodegradation of fluorene. External mass transfer effects were correlated with Colburn factor and Reynolds analogy. Abstract: The main objective of this study was to analyze the effects of the external mass transfer on fluorene (polycyclic aromatic hydrocarbon) degradation with immobilized LDPE (low-density polyethylene) in a packed bed bioreactor (PBBR). A most effective bacterial species Pseudomonas pseudoalcaligenes NRSS3 (MF9921912) was isolated from petroleum contaminated soil and immobilized on LDPE. The effect of different flow rates (10, 20, 30, 40, and 50 mL/h) on the degradation of fluorene was studied in a continuous PBBR. The overall removal efficiency of fluorene was found to be 88.49% in PBBR. The rate constants were estimated at different flow rates. The effect of flow rates on external mass transfer was also studied and correlated with the obtained experimental data. A correlation between Reynolds number (N Re ) and Colburn factor (JD ) ( J D = K N R e ( n - 1 ) ) was used to study the mass transfer aspects. The model was tested with various values of K, and n and based on experimental data, a new correlation J D = 5.71 N R e - 0.2 was obtained to predict the removal of fluorene in PBBR. The intermediate metabolites of the degraded sample were also analyzed by GC–MS and found that 1, 2-benzenedicarboxylic acid and catechol were formed during the biodegradation process.